2011
DOI: 10.1186/1752-1947-5-523
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal adhesion due to previous uterine surgery as a risk factor for delayed diagnosis of uterine rupture: a case report

Abstract: IntroductionUterine rupture is a life-threatening condition both to mothers and fetuses. Its early diagnosis and treatment may save their lives. Previous myomectomy is a high risk factor for uterine rupture. Intestinal adhesion due to previous myomectomy may also prevent early diagnosis of uterine rupture.Case presentationA 38-year-old primiparous non-laboring Japanese woman with a history of myomectomy was admitted in her 34th week due to lower abdominal pain. Although the pain was slight and her vital signs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 6 publications
0
9
1
Order By: Relevance
“…As was cited, we also previously reported a similar case of uterine rupture: the intestine/mesentery covered/occluded the rupture, preventing catastrophe. 2 The case described by Fukutani et al showed no bleeding, and rupture was revealed at term cesarean section, whereas our case had uterine contractions and hemoperitoneum, prompting preterm cesarean section. If the patient of Fukutani et al had experienced uterine contractions, rupture may have become larger, causing bleeding/hemoperitoneum, similar to our case.…”
contrasting
confidence: 45%
“…As was cited, we also previously reported a similar case of uterine rupture: the intestine/mesentery covered/occluded the rupture, preventing catastrophe. 2 The case described by Fukutani et al showed no bleeding, and rupture was revealed at term cesarean section, whereas our case had uterine contractions and hemoperitoneum, prompting preterm cesarean section. If the patient of Fukutani et al had experienced uterine contractions, rupture may have become larger, causing bleeding/hemoperitoneum, similar to our case.…”
contrasting
confidence: 45%
“…Uterine surgery, especially myomectomy, sometime causes adverse events in subsequent pregnancies. Of these, uterine rupture has been a major concern as previously described, 10,11 which may hold true also to adenomyomectomy. 5 Although we observed no causeeffect relation between adenomyomectomy and UAP, it is reasonable to assume it.…”
Section: Discussionmentioning
confidence: 93%
“…The case described by Dr. Kuwata et al also showed intestinal adhesion that covered and occluded a uterine rupture. Their case was symptomatic, while ours was asymptomatic . Dr. Matsubara and Dr. Morita suggested that, regardless of the clinical symptoms, the occlusion of a uterine rupture was dependent on the trigger: uterine contractions.…”
mentioning
confidence: 70%
“…Thus, the uterine rupture was not diagnosed until the patient underwent cesarean section. In the case described by Kuwata et al , intestinal adhesion might have masked the symptoms and signs and delayed the diagnosis . In another reported case, the incarcerated omentum occluded the uterine perforation after surgery in a patient who underwent dilatation and evacuation/curettage .…”
mentioning
confidence: 94%